Peran Pelatihan Kerja Dalam Meningkatkan Potensi Sumber Daya Manusia Pada Upt-Lk Wilayah I Provinsi Riau Menurut Perspektif Ekonomi Syariah - Kamal Hadi; Rozi Andrini; Sriyani Sriyani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper analyzes the role of job training in increasing the potential of human resources in UPT-LK Region I Riau Province according to a sharia economic perspective and explores the supporting and inhibiting factors in the implementation of job training. This study is essential considering that increasing the potential of human resources is an effort that must be made to compete in the world of work. One of the efforts that can be done to increase human resources' potential is by on-the-job training. This research is field research with qualitative descriptive analysis. The study results indicate that job training has a significant role in increasing the potential of human resources. The trainees stated that they had gained additional knowledge and skills. Factors supporting the implementation of job training at UPT-LK Region I Riau Province, including training materials, instructors, participants' abilities, funding, and strategic locations. While the inhibiting factors are related to facilities and infrastructure, some participants resigned during the training. There is no alumni association of training participants, so that there is no data on graduates who have worked according to the exercise that has been followed. The sharia economic review regarding the role of job training at UPT-LK Region I Riau Province, in general, is by sharia principles, namely kafa'ah, himmatul-Amal, and Amanah. Keywords: Role, Job Training, HR